Assessment of Effectiveness of Subsidized Food Grain Distribution in India with Respect to Rice and Wheat - A., Amudhasurabi; Jayas, Digvir S.; K., Alagusundaram (Indian Journal of Marketing, 2015)
This paper assessed the rationale of public policy intervention in rice and wheat markets in India. Specifically, this study compared the government's economic cost for subsidized distribution of rice and wheat with the domestic market prices to examine the economic viability of the public distribution system. The statistical grouping of domestic market prices of rice and wheat displayed a significant inter-year variation in the recent years from 2007 to 2011. The price increase was much higher for rice than for wheat. The government's economic costs for distribution of rice and wheat through the public distribution system were close to the domestic prices. The paper presents a critical analysis of the government's policy on subsidized grain distribution. Suggestions on government policy and the role of the private sector are explained in the Indian scenario. Furthermore, possibilities for price stabilization in the private food grain market, control over food inflation, and scope for tax revenues for government from the private sector are also discussed.